Land-cover dynamics and ecological carrying capacity of nature-based tourism in Tawangmangu Sub-District, Central Java, Indonesia - JAMILATUN NISA; IZA ADE FEBRIO; IVAN SETIAWAN; DIANTI DIANTI; CHEE KONG YAP; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nisa J, Febrio IA, Setiawan I, Dianti, Yap CK, Setyawan AD. 2026. Land-cover dynamics and ecological carrying capacity of nature-based tourism in Tawangmangu Sub-District, Central Java, Indonesia. Biodiversitas 27 (6): d270627. https://doi.org/10.13057/biodiv/d270627. Nature-based tourism in mountain landscapes requires systematic ecological evaluation because land-cover change and visitor pressure may progressively influence environmental stability. This study analyzed land-cover dynamics and activity-specific tourism carrying capacity in Tawangmangu Sub-district, Central Java, Indonesia, using five representative tourism sites distributed along an elevational gradient from 1,067 to 1,906 m asl. Land-cover composition was compared between 2015 and 2024 across five classes: vegetation, rice fields, built-up area, bare land, and green open space. Tourism carrying capacity was assessed through Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), and Effective Carrying Capacity (ECC) using accessible area, visitor space requirement, operational time, ecological and management correction factors, and management capacity. A project-level classification accuracy assessment yielded 87.6% overall accuracy and a kappa coefficient of 0.84; these metrics support broad landscape interpretation but do not imply precision for very small mapped changes. Vegetation remained dominant and increased from 3,121.48 to 3,327.35 ha (+6.59%), rice fields increased by 88.65 ha (+6.93%), green open space declined by 259.33 ha (-14.16%), and built-up area showed a small mapped net increase of 3.68 ha (+0.76%). To ensure numerical closure, overlay-derived transition proportions were reconciled to the independently mapped 2015 and 2024 class totals using iterative proportional fitting. Of the gross green-open-space area assigned to other classes in the reconciled matrix, 64.1% shifted to vegetation and 25.4% to rice fields, whereas only 1.6% shifted to built-up area. Corrected carrying-capacity calculations gave the highest ECC for trekking (816 visitors/day), followed by hiking (693), climbing (672), sightseeing (443), and camping (215). These results indicate a vegetation-dominated landscape with limited mapped net built-up change and strongly activity-dependent visitor-capacity scenarios; they should not be interpreted as evidence that tourism caused the observed land-cover changes. Management implications include vegetation retention, activity-specific visitor regulation, control of concentrated and long-duration use, and repeated spatial and ecological monitoring. The principal contribution is an integrated assessment that links mapped landscape dynamics, uncertainty-aware transition analysis, and activity-specific carrying-capacity scenarios within a single mountain tourism planning framework.